Influence of internet addiction on executive function and learning attention in Taiwanese school‐aged children. - Kuo, Shu‐Yu; Chen, Yu‐Ting; Chang, Yu‐Kai; Lee, Pi‐Hsia; Liu, Mei‐Ju; Chen, Su‐Ru (Perspectives in Psychiatric Care, 2018)
Purpose: This study aims to evaluate the executive function and learning attention in children with internet addiction (IA). Design and Methods: Children aged 10–12 were screened by Chinese Internet Addiction Scale to compose the IA group and internet nonaddiction group. Their executive functions were evaluated by Stroop color and word test, Wisconsin card sorting test, and Wechsler digit span test. Learning attention was evaluated by Chinese concentration questionnaire. Findings: Executive function and learning attention were lower in the IA group than in the internet nonaddiction group. Practice Implications: Executive function and learning attention are compromised by IA in children. Early interventions into the IA should be planned to maintain the normal development of executive function and learning attention in childhood.